PEMBERDAYAAN SOFT SKILLS GENERASI Z MELALUI KEGIATAN PELATIHAN SENI KRIYA MAKRAME - Fivanda; Natashya Iskandar; Gwendolyn Chelsea Josephine; Jennifer Hung; Vanesa (Jurnal Serina Abdimas, 2025)
Generation Z, born between 1997–2012, is inseparable from technology in both learning and working environments. As part of the productive age group, they hold significant potential to drive economic growth through local creative industries. One effective method to empower this generation is through soft skill development using macrame crafts. Macrame activities not only enhance creativity but also improve focus, patience, and perseverance. In facing the challenges of the digital era, soft skill empowerment supports career readiness, productivity, and social networking. Collaborative initiatives between institutions play a crucial role in facilitating craft training for Generation Z. One such initiative is the macrame craft training program, aimed at creating products with creative, commercial, and innovative value. This program aligns with SDGs Goal 4 (Quality Education) and Goal 8 (Decent Work and Economic Growth) by equipping youth with valuable life skills. In partnership with Yayasan Rumah Pagi Bahagia in Bintaro, this program specifically targeted foster children aged 13–16 years. The face-to-face training involved 20 participants and was conducted in two main stages: preparation and implementation. The preparation stage included surveys, interviews, and material distribution, followed by hands-on implementation. Guided by the PKM team, instructors demonstrated macrame knotting techniques and assisted participants in creating wall decoration pieces. This activity not only required attention to detail but also fostered perseverance. The outcome of this empowerment initiative is expected to contribute to the growth of innovative local creative products, even amidst the fast-paced advancement of artificial intelligence technology. ABSTRAK Generasi Z merupakan generasi yang tidak terlepas dari teknologi, baik dalam belajar maupun bekerja. Lahir pada tahun 1997–2012, Generasi Z termasuk usia produktif dan menjadi peluang untuk mempercepat pertumbuhan ekonomi melalui industri kreatif lokal. Pemberdayaan soft skills melalui seni kriya makrame menjadi sarana untuk mengembangkan kreativitas, meningkatkan fokus, dan melatih kesabaran. Dalam menghadapi tantangan dunia digital, penguatan soft skills dapat menambah peluang karir, produktivitas, serta memperluas jejaring sosial. Berbagai institusi berkolaborasi dalam penyelenggaraan pelatihan seni kriya bagi Generasi Z. Salah satunya adalah pelatihan kriya makrame yang bertujuan menghasilkan produk bernilai kreatif, komersial, dan inovatif. Kegiatan ini mendukung tercapainya tujuan SDGs ke-4 (pendidikan berkualitas) dan SDGs ke-8 (pekerjaan layak dan pertumbuhan ekonomi) dengan membekali generasi muda keterampilan yang bermanfaat di masa depan. Bersama mitra Yayasan Rumah Pagi Bahagia di Bintaro, kegiatan ini menyasar anak asuh berusia 13–16 tahun. Pelatihan dilakukan secara tatap muka kepada 20 peserta dan dibagi menjadi dua tahap, yaitu tahap persiapan dan tahap pelaksanaan. Tahap persiapan mencakup survei, wawancara, dan distribusi material, dilanjutkan dengan tahap pelaksanaan berupa demonstrasi langsung teknik menyimpul makrame oleh instruktur dari tim PKM. Pelatihan pembuatan dekorasi dinding makrame menuntut ketelitian dan ketekunan peserta. Hasil dari kegiatan ini diharapkan terus mendorong berkembangnya produk kreatif lokal yang inovatif di tengah pesatnya perkembangan teknologi kecerdasan buatan.